Commanding right and forbidding wrong? Al-Tabari’s representation of Al-Walid b. ‘Uqba as criticism of the Hanbalis - Su, I-Wen (Penerbit Universiti Kebangsaan Malaysia, 2018)
In his account of al-Walid b. ‘Uqba’s (d. 680) Kufan governorship, al-Tabari (839-923) presents al-Walid b. ‘Uqba as an ideal Muslim governor, whose rule was highly celebrated by Kufans of different social strata. He was dismissed in disgrace, however, due to the conspiracy of some Kufans, who maliciously accused him of drinking. It seems that the Tarikh is the only existing early compilation that ever presents al-Walid b. ‘Uqba in this light, whereas other early compilers more or less agree on the opposite version of the story — al-Walid b. ‘Uqba was truly an alcoholic. This paper addresses al-Tabari’s purpose in favouring Sayf b. ‘Umar’s positive account about al-Walid by first establishing that the other version of the story, on ‘Umar b. Shabba’s authority, was indeed available to al-Tabari, but was not used in the Tarikh. Then, the narrative of al-Walid b. ‘Uqba’s governorship is studied in connection with al-Tabari’s conflicts with the Hanbalis and the social turmoil they caused. This article argues that this unusual portrayal of al-Walid b. ‘Uqba can be read as al-Tabari’s criticism of the Hanbalis’ abuse of ‘commanding right and forbidding wrong’ (al-amr bi-l-maʿruf wa-l-nahy ʿan al-munkar).